EMPLOYMENT TRANSITIONS OF EGYPTIAN WOMEN IN TIMES OF CRISIS - El Assiouty, Souraya (AUC Knowledge Fountain, 2022)
The labor force participation of Egyptian women has been chronic economic problem in Egypt. Despite the improvement on the human capital front, whether on the education or health indicators, the female labor force participation remains persistently low. Using the data from the Egyptian Labor Market Panel Survey (ELMPS), this paper aims to identify the factors that influence, and the probability of women being employed, and to look at the transitions of women between the different employment statuses across the years using historic data from 2006-2018. The paper relies on the logit regression model that identifies the factors affecting the probability of women being employed. The results indicate that women’s transition in the labor market is not smooth, and being out of the labor force is often a sticky state. Women are not monogenous groups, and the factors affecting each work status transition vary greatly. Education is a main determinant of women’s employment, marriage and the presences of dependents in the household are among the factors that significantly reduce the chances of women of being employed, confirming that women in Egypt face a tradeoff between their productive and reproductive roles in the society.